The dependence of the anticipation of the executive operation task on spatial factors - Jovaiša , T. R.; Lapė , J. (Psichologija, 1985)
The present study deals with the dependence of the objective operation localization on the positioning of human being in the distance and on the degree of training certain movements. To this end, three series at experiments have been carried out, covering the effects of 6 factors (distance, direction of hand’s movement, direction of transition from one distance to another, degree of training, the start of hand’s movement, changing the hand’s movement direction). The results of the investigation showed that objective can be achieved in terms of spatial representation of surface. The image has the straight perpendicular line reflected as inclined. The process of training objectifies the spatial notion of surface.